In-situ synthesis and integration of gold nanoparticles into 3D printed optical fiber probes - Dileep Chekkaramkodi; Said El Turk; Murad Ali; Haider Butt (Scientific Reports)
Abstract This work uses the polymeric reduction method to explore the in-situ synthesis of gold nanoparticles (AuNPs) within 3D-printed optical fiber probes (OFPs). Digital light processing (DLP) 3D printing is employed to fabricate the OFPs using a resin consisting of hydroxyethyl methacrylate (HEMA) and polyethylene glycol diacrylate (PEGDA). After printing, OFPs were immersed in a boiling gold precursor solution to facilitate the synthesis of AuNPs inside the polymer matrix. We produced single material (HEMA/PEGDA) and multimaterial (HEMA/PEGDA + Dentaclear) OFPs loaded with AuNPs at different concentrations. Scanning electron microscopy analysis confirmed the effective distribution and dispersion of AuNPs within the polymer matrix. The optical properties, including reflection and transmission spectra, are comprehensively measured using customized setups. The localized surface plasmon resonance of the embedded AuNPs created a distinct dip in the 500–600 nm wavelength range. Higher AuNP concentrations and longer dipping times enhanced light absorption, reducing reflection and transmission intensities. Multimaterial OFPs also exhibited tunable wavelength filtering capabilities based on the AuNP concentration. The AuNP-loaded OFPs demonstrated stable optical performance across varying temperatures and pH environments, highlighting their potential for diverse applications.